Cover Image. (19th June 2020) - Wyatt, Kevin H.; Rober, Allison R.; Pope, Cody A.; Halvorson, Halvor M.; Findlay, Robert H.; Francoeur, Steven N.; Kuehn, Kevin A.
Abstract : The cover image is based upon the Original articles Warming enhances the stimulatory effect of algal exudates on dissolved organic carbon decomposition by Kevin H. Wyatt and Allison R. Rober, https://doi.org/10.1111/fwb.13390 (top left image) and Light and temperature mediate algal stimulation of heterotrophic activity on decomposing leaf litter by Cody A. Pope et al., https://doi.org/10.1111/fwb.13465 (right and bottom left images).